Analysis of the Level of Responsiveness of Local Government Public Services through Social Media - SOANTAHON, Sherwin Mikhael (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: This study aims to analyze the level of responsiveness of local government public services through social media. This issue was raised due to the increasing trend of social media use by the public and the potential for providing public services to the community through social media. In this study, we will look at the level of responsiveness of local government agencies, especially city governments, in serving people who request public services through social media.Methodology:This research uses a mixed approach (mixed method) with sample selection using random sampling techniques based on area (cluster random sampling). The sample used comes from representatives of the Regional Government from the city level based on the division of the western, central, and eastern parts of Indonesia.Findings:The results of this study indicate that the level of responsiveness of local government public services through social media is still low. The sample analysis results in this study show that only 10.71% of official local government social media accounts respond to complaints/submissions of public services through social media.Implication:From the results of this study, the level of responsiveness of local government public services is still relatively low. It can hurt the quality and image of public services by the Regional Government.